(untitled) (Educational Knowledge, 2019)
At the secondary school of the El Volcán Departmental Educational Institution in the municipality of Ubaté, Colombia, an action research project was conducted with a qualitative and descriptive approach. The project focused on transforming pedagogical practices to develop critical thinking skills, such as interpretation and explanation, based on the teaching for understanding approach. The process of transforming pedagogical practices was analyzed, developing curricular proposals that fostered explanation and interpretation; designing pedagogical strategies based on the teaching for understanding approach; and evaluating the impact of these strategies on students’ critical thinking skills to promote comprehension. The study presents the improvement in tenth-grade students’ understanding of the subject matter in Chemistry, both in relation to the disciplinary content and the development of the aforementioned critical thinking skills, resulting from changes in the science teacher’s pedagogical practices in a rural setting. Therefore, a clear and coherent organization in the planning of classes (hereinafter, units of understanding), reflections on practice, continuous assessment of learning and the use of thinking routines, led to a significant improvement in the levels of understanding in the students.